Comparative Analysis of the Mutation and Expression Profile of the Cytoprotective NRF2/ KEAP1/P62/SQSTM1 Signaling Pathway in Different Glioma Subtypes: An In Silico Study - Dilara Fatma AKIN; Sedef Hande AKTAŞ (Namık Kemal Tıp Dergisi, 2023)

(untitled)
Aim:The NRF2/KEAP1/p62/SQSTM1 pathway is the master regulator of antioxidant enzymes and detoxification proteins, both of which play a critical role in redox homeostasis. It shows that the this structurally active pathway has a crucial role in cancer as it inhibits tumorigenesis and metastatic processes and it induces pro-survival genes that promote chemoresistance. The relationship between the molecular mechanisms causing the pathway to malfunction and the development of brain tumors has yet to be fully clarified. The aim of this study is to analyze the genetic changes and expression level differences of the NRF2/KEAP1 pathway comparatively in low-grade gliomas (LGG) and glioblastoma multiforme (GBM) pathology.Materials and Methods:Gene expression profiles and DNA sequences of GBM (n=591) and LGG (n=511) patients and healthy tissue were downloaded from the TCGA database. Not only were gene expression and mutation patterns determined in this study, but also the impacts of genes on survival were assessed. PolyPhen-2 and SNAP tools were used to estimate the pathogenic properties of the changes identified.Results:A total of 16 mutations and gene amplification were identified in the KEAP1, NRF2, p62/SQSTM1, HMOX-1, and MOAP1 for both cancer groups, and the mutation carrying frequency was 4.6%. IDH1 p.R132H and NRF2 p.S164* mutation association was determined in 1 patient with LGG. KEAP1, NRF2, and HMOX1 expression levels for both LGG and GBM subtypes were determined to be high in patient samples compared to healthy samples (p<0.05).Conclusion:By targeting the NRF2/KEAP1/p62/SQSTM1 pathway anomalies, new therapeutic approaches can be provided in the treatment of glioma, particularly for chemotherapy sensitivity.